"Heroes never die": the constitution of the rapper's social position at the beginning of the 21st century (PerCursos, 2024)
The article aims to reflect on the constitution of the symbolic position of the Brazilian rapper from the beginning of the 21st century, analyzing two songs by groups from this period: "Us heróis não morrem", by Alvos da Lei; and "Programado pra morre", by Trilha Sonora do Gueto. The aim is to reflect on the symbolic force of this artistic production, which brings revelations about society, accommodates characters in specific ethical conducts, attributes and offers meanings, categories and senses that come to life beyond the musical genre and which, in this sense, characterize the rapper's charisma.
Keywords: popular music; rap; brazilian popular culture; brazilian rapper; symbolic production